Left renal vein transposition is effective for posterior nutcracker syndrome - Chen, Yuedong (Int J Clin Exp Med, 2014)
An 8-year-old girl was enrolled in hospital with intermittent gross hematuria in a period of 3 years. Bloody efflux from the left ureteral orifice was diagnosed in this patient with urethrocystoscopy. A retroaortic left renal vein appeared to be compressed by the aorta as detected by computerized tomography. The left renal vein was compressed between the aorta and the spine. A groove in the anterior surface of the left renal vein was detected. A transposition surgery of the left renal vein to a site in front of the aorta was performed for the patient. The patient was discharged after recovery and the hematuria symptom was not found during the 15-month follow-up investigation.